Cardiac transplantation in adult congenital heart disease with prior sternotomy. Issue 4 (6th March 2021) - Kainuma, Atsushi; Ning, Yuming; Kurlansky, Paul A.; Axsom, Kelly; Farr, Maryjane; Sayer, Gabriel; Uriel, Nir; Lewis, Matthew J.; Rosenbaum, Marlon S.; Kalfa, David; LaPar, Damien J.; Bacha, Emile A.; et al.
Abstract: Background: Adult congenital heart disease (ACHD) patients who require orthotopic heart transplantation are surgically complex due to anatomical abnormalities and multiple prior surgeries. In this study, we investigated these patients' outcomes using our institutional database. Methods: ACHD patients who had prior intracardiac repair and subsequent heart transplant were included (2008–2018). Adult patients without ACHD were extracted as a control. A comparison of patients with functional single ventricular (SV) and biventricular (BV) hearts was performed. Results: There were 9 SV and 24 BV patients. The SV group had higher central venous pressure/pulmonary capillary wedge pressure ( P = .028), hemoglobin concentration ( P = .010), alkaline phosphatase ( P = .022), and were more likely to have liver congestion ( P = .006). Major complications included infection in 16 (48.5%), temporary dialysis in 12 (36.4%), and graft dysfunction requiring perioperative mechanical support in 7 (21.2%). Overall in‐hospital mortality was 15.2%. Kaplan‐Meier analysis showed a higher, but not statistically significant, survival after 10 years between the ACHD and control groups (ACHD 84.9% vs. control 67.5%, P = .429). There was no significant difference in 10‐year survival between SV and BV groups (78% vs. 88%, P = .467). Conclusions: Complex ACHD cardiac transplant recipients have a high incidence of early morbidities after transplantation. However, long‐term outcomes were acceptable.